2018
DOI: 10.15208/beh.2018.42
|View full text |Cite
|
Sign up to set email alerts
|

Board diversity, audit committee characteristics and audit quality: The moderating role of control-ownership wedge

Abstract: This study illustrates how control-ownership wedge impacts the monitoring role of the corporate board through the quality of audit services in Turkey. Turkey has made essential amendments in the field of external audit in order to enhance the quality of the financial report and integrate its own capital market with that of the EU. It would be of interest to examine the influence of these changes on clients' demand for high quality audit. The agency theory is integrated with the resource dependence theory to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 88 publications
(108 reference statements)
5
33
0
2
Order By: Relevance
“…The board of directors" size (BODSIZE) is measured by the total number of executive and non-executive directors on the board at the end of the fiscal year. Both Agyei-Mensah 2016and Mustafa et al (2018) found a positive association between board size and audit quality, and between board size and disclosure quality. They argue that more directors on the board provide more resources and experience, which will enhance board monitoring ability, enhance information transparency and increase the amount of information disclosed in annual reports.…”
Section: Control Variablesmentioning
confidence: 95%
See 2 more Smart Citations
“…The board of directors" size (BODSIZE) is measured by the total number of executive and non-executive directors on the board at the end of the fiscal year. Both Agyei-Mensah 2016and Mustafa et al (2018) found a positive association between board size and audit quality, and between board size and disclosure quality. They argue that more directors on the board provide more resources and experience, which will enhance board monitoring ability, enhance information transparency and increase the amount of information disclosed in annual reports.…”
Section: Control Variablesmentioning
confidence: 95%
“…Board of directors" financial expertise (BODFX) was coded 1 if more than half of the board members had finance or accounting experience and 0 otherwise. Mustafa et al (2018) found that board members with financial background and experience tend to demand better audit services to enhance their monitoring capabilities over management. Besides, the board of director's independence (BODIND) measured by the number of non-executive directors on the board.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…independent directors among the board. According to Agyei-Mensah (2019) and Mustafa et al (2018) study results, independent board members tend to provide external pressure to enhance firm performance, lower levels of financial reporting problems, and increase disclosure levels.…”
Section: Control Variablesmentioning
confidence: 99%
“…Most firms are not listed on stock exchanges and even when they are, a single large shareholder or a small group of shareholders retains a controlling share in the firm (Mustafa, Che-Ahmad, & Chandren, 2018). Since the concentrated ownership structure makes firms impervious to takeovers, the controlling stake commonly stays with the founder of the company and his family, even when the company is large and publicly listed.…”
Section: Introductionmentioning
confidence: 99%